Gut hormones, adipokines, and pro- and anti-inflammatory cytokines/markers in loss of control eating: A scoping review. (1st November 2021) - Yu, Yang; Fernandez, I. Diana; Meng, Ying; Zhao, Wenjuan; Groth, Susan W.
Abstract: Loss of control (LOC) eating is the defining feature of binge-eating disorder, and it has particular relevance for bariatric patients. The biomarkers of LOC eating are unclear; however, gut hormones (i.e., ghrelin, cholecystokinin [CCK], peptide YY [PYY], glucagon-like peptide 1 [GLP-1], and pancreatic polypeptide [PP]), adipokines (i.e., leptin, adiponectin), and pro- and anti-inflammatory cytokines/markers (e.g., high-sensitivity C-reactive protein [hsCRP]) are candidates due to their involvement in the psychophysiological mechanisms of LOC eating. This review aimed to synthesize research that has investigated these biomarkers with LOC eating. Because LOC eating is commonly examined within the context of binge-eating disorder, is sometimes used interchangeably with subclinical binge-eating, and is the latent construct underlying disinhibition, uncontrolled eating, and food addiction, these eating behaviors were included in the search. Only studies among individuals with overweight or obesity were included. Among the identified 31 studies, 2 studies directly examined LOC eating and 4 studies were conducted among bariatric patients. Most studies were case-control in design (n = 16) and comprised female-dominant (n = 13) or female-only (n = 13) samples. Studies generally excluded fasting total ghrelin, fasting CCK, fasting PYY, and fasting PP as correlates of the examined eating behaviors. However, there was evidence that the examined eating behaviors were associated with lower levels of fasting acyl ghrelin (the active form of ghrelin) and adiponectin, higher levels of leptin and hsCRP, and altered responses of postprandial ghrelin, CCK, and PYY. The use of GLP-1 analog was able to decrease binge-eating. In conclusion, this review identified potential biomarkers of LOC eating. Future studies would benefit from a direct focus on LOC eating (especially in the bariatric population), using longitudinal designs, exploring potential mediators and moderators, and increased inclusion of the male population.